Body composition, aerobic fitness, isokinetic profile, and vertical jump ability in elite male and female volleyball and beach volleyball players - Freire, R.; Hausen, M.; Pereira, G.; Itaborahy, A. (Journal of Science in Sport and Exercise, 2023)
Purpose This study aimed to compare the physical attributes of male and female Volleyball and Beach Volleyball athletes.